Bimodal classification of natural specializations as a neurophysiological basis of dichotomous typologies: A comparative analysis with MBTI - Ishkov, Aleksandr (Edelweiss Applied Science and Technology, 2026)
The article presents a theoretical and methodological substantiation of the Bimodal Classification of Natural Specializations (CNS-B) and its comparative analysis with the Myers–Briggs Type Indicator (MBTI). The study aims to identify fundamental differences between the phenomenological description of personality preferences in the MBTI and the neurophysiologically grounded CNS-B model, which is based on the principle of alternative paired regulation of activity. The methodological approach used in the CNS-B allows for a strict separation of the cognitive and functional-regulatory levels of description. The CNS-B introduces and theoretically substantiates the concepts of natural and artificial activity specializations. The main results include a structural representation of the CNS-B through four dichotomies forming 16 integral natural specializations, and their comparison with MBTI types. It is demonstrated that the instability of typing in the MBTI is explained by its sensitivity to compensatory behavioral profiles, whereas the CNS-B captures a stable neurophysiological foundation. A comparative analysis of the 16 integral CNS-B specializations and MBTI types reveals partial and asymmetric correspondence, highlighting the limitations of the phenomenological approach. The conclusion substantiates the possibility of using the CNS-B as a metatheoretical framework for interpreting and refining the results of dichotomous typologies.